Hyperparathyroidism in a renal transplant patient: an unusual cause of resistance to therapy. (13th August 2012) - Somalanka, Subash; Phanish, Mysore K
Abstract : A long-term renal transplant patient who was regularly followed up in the transplant clinic with stable renal allograft function was found to have elevated parathyroid hormone (PTH) levels on a biointact PTH assay. The elevated PTH levels were resistant to suppression on increasing doses of 1-alfacalcidol. Detailed history taking and clinical examination revealed the reason for apparent resistance to therapy.